Encouraging students' engagement and promoting deep learning in immunology through an interactive clinical case problem-solving (CCPS) approach: Perception among cohort of medical students in Oman - Mohan B Sannathimmappa; Vinod Nambiar; Rajeev Aravindakshan (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Modern competency-based medical education emphasizes student-centered teaching-learning strategies where students take responsibility of their own learning. Student-centered approaches facilitate multifaceted learning such as observation, critical evaluation, analysis, deeper understanding, and application of knowledge. The current study aims at assessing the students' perception on utilization of clinical case problem-solving approach (CCPS) to promote their lifelong learning. MATERIALS AND METHODS: The present cross-sectional study was conducted at College of Medicine and Health Sciences (CoMHS) during the year 2021-2022. MD3 students of the academic year 2021-2022 were the study participants. The study was approved by institutional Ethic and Review Committee. Students' performances were assessed through pre-test and post-test performances. Students' feedback was collected through a predesigned questionnaire on a 3-point Likert scale. Cronbach's alpha coefficient test was used to assess the reliability of the questionnaire. The data was entered to Microsoft Excel and analyzed using SPSS software version 22. Paired t-test was used to compare pre-test and post-test scores and the data was expressed as numbers and percentages. RESULTS: In total, 103 participants were included in the study. Post-test scores were significantly higher compared to pre-test scores (p < 0.05). Questionnaire results showed that CCPS approach was accepted as an effective learning strategy. Majority (>90%) of the students expressed CCPS approach was interesting, motivated to learn, encouraged peer discussion, enhanced knowledge, and clarified their topic-related doubts. More than 80% students opined that CCPS enhanced their critical thinking, problem-solving ability, deep learning, and lifelong learning skills. Nearly 90% of the students suggested for including such sessions for more topics in immunology course in future. CONCLUSION: From our study results, it can be concluded that CCPS is an effective learning strategy to encourage students' engagement and promote their deep learning skills.